Deconstructing mptcp performance - Arzani, Behnaz; Gurney, Alexander; Cheng, Sitian; Guerin, Roch; Loo, Boon Thau (Network Protocols (ICNP), 2014 IEEE 22nd International Conference on, 2014)
Deconstructing MPTCP performance Behnaz Arzani, Alexander Gurney, Sitian Cheng, Roch Guerin, Boon Thau Loo The paper seeks to broaden our understanding of MPTCP and focuses on the impact that initial sub-path selection can have on performance. Using empirical data, it demonstrates that which sub-path is chosen to start an MPTCP connection can have unintuitive consequences. Using numerical analysis and a model-driven investigation, the paper elucidates and validates the empirical results, and highlights MPTCP's non-linear coupling between paths as a primary cause for this behavior. The findings are both of operational interest and may help design better MPTCP schedulers, as they are also exposed to complex interactions with MPTCP's congestion control.